2020
DOI: 10.1021/acs.chemrestox.0c00339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Noncanonical Necrotic Cell Death Triggered via Enhanced Proteolysis by a Novel Sapogenol Derivative

Abstract: Small molecules which activate distinct cell death pathways have promising high potential for anticancer drug research. Especially, regulated necrosis draws attention as an alternative cell death mechanism to overcome the drug resistance. Here, we report that a new semisynthetic saponin analogue (AG-08) triggers necrotic cell death with unprecedented pathways. AG-08-mediated necrosis depends on enhanced global proteolysis involving calpains, cathepsins, and caspases. Moreover, AG-08 generates several alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Interestingly, CHOP protein level was enhanced by 8 µM AG-08 treatment but surprisingly decreased by 16 µM (Figure 6B). Since similar results was observed in the p62 protein levels in the previous study [1], we suggested that the CHOP levels were induced due to ER stress, but the enhancement of proteolysis by the prolonged or higher dose treatments of AG-08 might lead to degradation of full-length CHOP protein.…”
Section: Ag-08 Particles Induce Uprsupporting
confidence: 87%
See 3 more Smart Citations
“…Interestingly, CHOP protein level was enhanced by 8 µM AG-08 treatment but surprisingly decreased by 16 µM (Figure 6B). Since similar results was observed in the p62 protein levels in the previous study [1], we suggested that the CHOP levels were induced due to ER stress, but the enhancement of proteolysis by the prolonged or higher dose treatments of AG-08 might lead to degradation of full-length CHOP protein.…”
Section: Ag-08 Particles Induce Uprsupporting
confidence: 87%
“…After the discovery of regulated necrosis, the induction of necrotic cell death has attracted huge attention and numerous studies state that necrotic death inducers possess high potential for cancer treatment. In a recent study, we reported a new semi-synthetic saponin analog (AG-08) triggering necrotic cell death along with unprecedented pathways including enhancement of global proteolysis and several alterations in lysosomal function and physiology [1]. The subsequent studies revealed an unexpected property of AG-08: After one freeze thaw cycle of its solution, AG-08 lost its cytotoxicity without any change in its chemical structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…HEKn cells were seeded on 6 well plate with coverslips for fluorescence microscopy (Uner et al, 2020). The next day, cells were treated with the indicated concentration of CA for 24 h. Then, cells on coverslips were washed twice with cold 1X PBS and fixed with 4% paraformaldehyde in PBS for 30 min at 4°C.…”
Section: Immunofluorescence Analysismentioning
confidence: 99%